Valores corporativos en la Empresa Grupo Ronquillo Sandoya de la ciudad de Babahoyo. Período 2022. - Riquero Carpio, Emely Denisse (2023)
Through this case study called Corporate Values of the company Grupo Ronquillo Sandoya. Period 2022. Same as it is related to the line of research Information and communication systems, entrepreneurship and innovation and is contextualized in the subline of Companies and public and private institutions due to the fact that the company is dedicated to the commercialization of drugs, this work was carried out with the objective of analyzing the corporate values of the organization, determining their degree of application and identifying corporate communication and punctuality. For the development of the case study, it was necessary to implement two techniques, which were the interview with the administrative manager and the survey of the company's employees. The methodology of the present work was based on the qualitative and quantitative paradigmatic modalities together with the implementation of the analytical method and the deductive method, which helped to discern the case study. This allowed obtaining the results that were exposed in their respective section. , it should be noted that these results are those expectations set forth in the objectives of the work, since they were the guide for its development.